Estimating the modulating role of economic development on the effect of elections on government expenditure in Africa - Serebour Quaicoe (Cogent Economics & Finance, 2022)
The study contributes to the political economy debate in Africa by examining the extent to which economic development mediates the effect of elections on government expenditure. To this end, the study employs macrodata spanning 1985-2015 on 43 African countries for the analysis. Robust evidence from the system GMM estimator shows that: (1) election periods significantly induce government expenditure in Africa, and (2) economic development is significant in reducing the use of fiscal surprise in election periods. Policy recommendations are provided in the end.
Keywords: 330; Africa; Budget Cycle Hypothesis; Democracy; Economic Development; Election; Election Burden; Government Expenditure